Feasibility study of locomotion training in a home-visit preventive care program - Kimura, Midori; Nakamura, Kozo; Fujino, Keiji; Yasumura, Seiji; Ito, Hiromoto; Nakano, Kyoko; Hashimoto, Mari (Nihon Rōnen Igakkai zasshi, 2012)
Aim: To evaluate the feasibility of locomotion training (single-leg standing and squats) in a home-visit preventive care program for the elderly. Methods: We invited 246 people who were not attending any preventive care programs within the long-term care insurance system. Among these, 60 participated in the current program. We administered a hearing survey, measured the single-leg stance time with eyes open, and subjects underwent locomotion training. Each participant was asked to repeat 1 set of training exercises 3 times per day at home. One set consists of standing on each leg for 1 minute and squatting 5 to 6 times. We telephoned the participants regularly during the 3 month program (locomo call). At the end of the program, we visited the participants and measured the single-leg stance time with eyes open. Results: A total of 60 elderly adults participated in the program (15 men, 45 women). Among subjects secondary prevention of musculoskeletal (n=313), 67 were participating in site-visit preventive care programs conducted by the local authorities (21.4%). Among these 313, 127 were participating in site-visit preventive care programs or locomotion training (40.6%). It shows the increasing of the participation rate 21.4% to 40.6%. The continuance rate was 91.7%. The single-leg stance time improved for both men (16.2±17.7 sec, p<0.05) and women (57.2±79.7 sec, p<0.01) compared to the baseline. Similarly, improvement was observed in the single-leg stance time for both the young-old (62.2±67.9 sec, p<0.01) and the old-old (39.2±73.8 sec, p<0.01). Conclusions: We consider that the locomotion training program which we introduced in the current home-visit preventive care program was effective and highly feasible for the elderly who have not previously responded conventional site-visit preventive care programs.